Énoncé de mission. (Nouvelles Perspectives en Sciences Sociales, 2026)
The article presents the journal *Nouvelles perspectives en sciences sociales* (NPSS), which aims to support researchers exploring new approaches in the social sciences. NPSS encourages rigorous analyses capable of going beyond established models, notably through the adoption of complex systems theory and relational analysis. These approaches prioritize the study of dynamics and connections between elements of a whole, rather than the isolated analysis of objects, thus offering an interdisciplinary perspective. The journal promotes openness to any innovative reflection, emphasizing the importance of moving beyond hasty criticisms of these methods in the social sciences.